Stakeholder involvement in the development of genetically modified (GM) food labelling policy in South Africa - De Beer, Taryn Lynne (Department of Environmental and Geographical Science, 2016)
Like many other countries worldwide, South Africa has come under public pressure to introduce mandatory GM labelling. Although there is an increased understanding about the social and political implications of GM labelling in developed countries, there is still a research gap with regard to implications for developing countries. South Africa, as a country that consumes, produces and trades GM food, represents a fitting case study to investigate these dimensions in the context of a developing economy. There has been very little understanding about how the mandatory labelling law for GM food developed in South Africa. This study, thus, aims to analyse how this policy developed and has been implemented in South Africa, in order to draw wider conclusions about GM food labelling in developing countries. This has been achieved through review of the relevant literature, in-depth interviews with 27 stakeholders from industry, government, NGOs and the academic and scientific community, and document analysis. A stakeholder analysis approach was used for framing and informing the research findings of this study. This framework provided a stakeholder perspective through which to examine the policy development process of mandatory GM labelling. Findings from this research project reveal that the policy governing the mandatory labelling of GM foods in South Africa was developed and shaped by many significant events and decisions. However, the law evolved within a context of conflict from a diversity of stakeholders. Stakeholders, who participated in and contributed towards the process, had their own degree of "interest and power", which influenced and impacted on the GM labelling policy-making and the implementation processes. Research revealed that there were important issues that emerged during the policy development and implementation phases. These included: the effectiveness of stakeholder participation; the use of a "may contain" label; the percentage of the threshold level; and labelling costs. The stakeholders' viewpoints on each of these issues differed among different groups.